Effects of stand types on recreational preferences of society in the Sub-Alpine Zone, northern Turkey - Varol, Tuğrul; Özel, Halil Barış; Kara, Ferhat; Çavuş Kara, İlkim; Ayan, Sezgin (Springer Science and Business Media LLC, 2022)
The main objective of this study was to examine how different stand types influenced the tendency of visitors for varying recreational activities (i.e., hiking, trekking, camping and hunting) from 1993 to 2018 in the surrounding areas of Uluyayla Natural Recreation Site in Bartin, northern Turkey. A total of 627 visitors were selected on a voluntary basis, and questioned in the form of questionnaire. Most of the participants were in the age of 21-40 years old, and they were mostly (62.4%) male. Most of the participants (82.7%) lived in cities, while 62.8% of them were tourists when visiting the site. In determining the preferences of the visitors regarding the stand types for different recreational activities, several images of each stand were shared with them, and they were asked which stand type they would prefer for a given recreation activity (i.e., hiking, tracking, camping and hunting). A range of options from 1 to 5 in Likert's scale was used in evaluating the given responses. The degree of positive and negative effects was examined via trend analysis. It was found that stand type had influence on the preferences of visitors regarding the recreational activities. In general, unmanaged and moderately treated stands were more preferred by visitors for the recreational purposes, compared to the previously managed stands. On the other hand, visitors' preference for the activities were different during two periods (i.e., 1993-2005 and 2006-2018). For each recreational activity, there was an increasing trend from 1993 to 2018. There had been a continuous increase for hunting since 1996, and for trekking and camping after 1999. The increases between 1993-1996 and 1996-1999 were likely due to the increasing awareness of the society as a result of the training and consciousness raising activities for nature conservation. The demand on the recreational activities continuously increased in unmanaged and moderately treated stands, while no significant changes were examined in the previously managed stands. The study points out that forest planning and management should consider different needs of visitors for recreational infrastructure.
Keywords: Camping; National Park; Hunting; Recreation; Original Article; Silviculture; Subalpine; 15. Life on land